Hubungan antara Kecerdasan Spiritual dengan Resiliensi Akademik Siswa SMK di Semarang Utara - Etika Meiranti; Anwar Sutoyo (Indonesian Journal of Counseling and Development, 2020)
Academic resilience is important for students to have in their academic process. Based on preliminary research conducted by researchers, there was a low academic resilience, while spiritual intelligence tended to be high. This research aims to find out the relationship between spiritual intelligence and academic resilience of vocational school students in North Semarang. The type of research used in this study is quantitative correlational. Sampling using simple random sampling techniques. Instruments used for data retrieval are the psychological scale of academic resilience and spiritual intelligence. The data analysis used in the hypothesis test is Pearson's Product Moment correlational test. This study found that there is a significant positive relationship, with a strong degree of correlation between spiritual intelligence and academic resilience of vocational school students in North Semarang. The advice that researchers can give counselors is to provide services with the aim of improving academic resilience and spiritual intelligence, as well as implementing policies that support the development of spiritual intelligence and academic resilience.